Up to “Me” or Up to “Us”? The Impact of Self-Construal Priming on Cognitive Self-Other Integration - Colzato, Lorenza S.; De Bruijn, Ellen; Hommel, Bernhard (Frontiers in Psychology, 2012)
The degree to which people construe their perceived self as independent from or interdependent with their social environment can vary. We tested whether the current degree of social self-construal predicts the degree to which individuals integrate others into their self-concept. Participants worked through tasks that drew attention to either personal interdependence (e.g., by instructing participants to circle all relational pronouns in a text, such as “we”, “our”, or “us”) or independence (by having them to circle pronouns such as “I”, “my”, or “me”) and comparing them with respect to the social Simon effect (SSE)—an index of the degree to which people co-represent the actions of a co-actor. As predicted, the SSE was more pronounced in the interdependence group than in the independence group, suggesting that self-other integration varies dynamically as a function of the relative saliency of the other.